Assessment of haptic memory using somatosensory change‐related cortical responses. Issue 17 (26th August 2020) - Sugiyama, Shunsuke; Kinukawa, Tomoaki; Takeuchi, Nobuyuki; Nishihara, Makoto; Shioiri, Toshiki; Inui, Koji
Abstract: Haptic memory briefly retains somatosensory information for later use; however, how and which cortical areas are affected by haptic memory remain unclear. We used change‐related cortical responses to investigate the relationship between the somatosensory cortex and haptic memory objectively. Electrical pulses, at 50 Hz with a duration of 500 ms, were randomly applied to the second, third, and fourth fingers of the right and left hands at an even probability every 800 ms. Each stimulus was labeled as D (preceded by a different side) or S (preceded by the same side). The D stimuli were further classified into 1D, 2D, and 3D, according to the number of different preceding stimuli. The S stimuli were similarly divided into 1S and 2S. The somatosensory‐evoked magnetic fields obtained were divided into four components via a dipole analysis, and each component's amplitudes were measured using the source strength waveform. The results showed that the preceding event did not affect the amplitude of the earliest 20–30 ms response in the primary somatosensory cortex. However, in the subsequent three components, the cortical activity amplitude was largest in 3D, followed by 2D, 1D, and S. These results indicate that such modulatory effects occurred somewhere in the somatosensory processing pathway higher than Brodmann's area 3b. To the best of our knowledge, this is the first study to demonstrate the existence of haptic memory for somatosensory laterality and its impact on the somatosensory cortex using change‐related cortical responses without contamination from peripheral effects. Abstract : Electrical pulses were randomly applied to the right and left hands. The somatosensory‐evoked magnetic fields obtained were divided into four components (early SI, middle SI, late SI, and cSII). For each component, there are five event histories (1D, 2D, 3D, 1S, and 2S), which indicate the number of different (D) or similar (S) tactile stimuli that precede the probe stimulus.